3D‐T2W‐TSE radiotherapy treatment planning MRI using compressed sensing acceleration for prostate cancer: Image quality and delineation value. Issue 5 (24th January 2022) - Wong, Oi Lei; Poon, Darren M.C.; Kam, Miachael K.M.; Lo, Gladys G.; Fung, Winky W.K.; Man, Shei Yee; Xue, Cindy; Yu, Siu Ki; Cheung, Kin Yin; Yuan, Jing
Abstract: Purpose: To assess the image quality and delineation value of compressed sensing (CS)‐accelerated 3D T2W turbo‐spin‐echo (TSE) sequence for radiotherapy treatment planning (RTP) of prostate cancer. Methods: An optimized CS‐accelerated 3D‐T2W‐TSE was determined by volunteer imaging and applied for clinical RTP‐MRI. This optimized CS‐accelerated planning MRI and the standardized adaptive MRI acquired at 1.5T were retrospectively analyzed in 26 prostate cancer patients who were to receive MR‐guided radiotherapy. Signal‐to‐noise ratio (SNR) and relative contrast ratio (CR) were quantitatively assessed. Image quality and artifacts were qualitatively assessed using a five‐point scale rating. Delineation value in the prostate and organs‐at‐risk (OARs) was also rated and compared. Wilcoxon signed‐rank test was used for SNR, relative CR, and rating comparisons. The interobserver rating agreement was evaluated by percent agreement. Results: Significantly better SNR and relative CR in the prostate, rectum, bowel, penis, and penile bulb, while significantly worse in the cauda equina, were observed on the planning MRI. Significantly better ratings of image quality and artifacts were given to the planning MRI, with much less Gibbs ringing and reconstruction artifacts. Significantly better delineation value rating was achieved on the planning MRI in the prostate, seminal vesicle, rectum, penis, penile bulb, and testes, while significantly worse in the cauda equina. A strong to almost perfect interobserver rating agreement was obtained. Conclusion: This study suggested that CS acceleration is applicable and valuable in prostate RTP‐MRI. CS‐accelerated 3D‐T2W‐TSE images should benefit the delineation of prostate and many OARs. Abstract : CS was utilized for radiotherapy planning MRI acceleration Superior quality 3D‐T2W‐TSE prostate planning MRI was obtained by CS acceleration CS‐planning MRI achieved better delineation value rating in prostate and many OARs